Investigating the Temperature Dependency of Trimethyl Aluminum Assisted Atomic Surface Reduction of Li and Mn-Rich NCM - Evenstein E.; Taragin S.; Saha A.; Noked M.; Rosy (My University, 2025)
Most next-generation electrode materials are prone to interfacial degradation, which eventually spreads to the bulk and impairs electrochemical performance. One promising method for reducing interfacial degradation is to surface engineer the electrode materials to form an artificial cathode electrolyte interphase as a protective layer. Nevertheless, the majority of coating techniques entail wet processes, high temperatures, or exposure to ambient conditions. These experimental conditions are only sometimes conducive and can adversely affect the material structure or composition. Therefore, we investigate the efficacy of a low-temperature, facile atomic surface reduction (ASR) using trimethylaluminum vapors as a surface modification strategy for Li and Mn-rich NCM (LMR-NCM). The results presented herein manifest that the extent of TMA-assisted ASR is temperature-dependent. All tested temperatures demonstrated improved electrochemical performance. However, ASR carried out at temperatures >100 °C was more effective in preserving the structural integrity and improving the electrochemical performance. Electrochemical testing revealed improved rate capabilities, cycling stability, and capacity retention of ASR-treated LMR-NCM. Additionally, post-cycling high-resolution scanning electron microscopy analysis verified that after extended cycling, ASR carried out at T > 100 °C showed no cracks or cleavage, demonstrating the efficiency of this method in preventing surface degradation. © 2024 The Electrochemical Society (“ECS”). Published on behalf of ECS by IOP Publishing Limited.